2014
DOI: 10.3922/j.psns.2014.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological factors associated with cognitive deficits in children with ADHD symptoms: EEG and neuropsychological analysis.

Abstract: We neuropsychologically assessed cognitive deficits in 109 children with symptoms of attention-deficit/hyperactivity disorder (ADHD) and 51 children with typical development aged 7-8 years and 9-10 years and visually analyzed resting-state electroencephalography (EEG). The EEG recordings of children with ADHD more frequently contained EEG patterns of frontothalamic non-optimal functioning compared with controls, reflected by groups of bilaterally synchronous frontal theta waves (FTWs) and right hemisphere loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
0
13
0
2
Order By: Relevance
“…At the same time, it is not correct to suppose that each cases of attention deficit disorder have always the same constellation of symptoms, central mechanisms and actions. Previous experience and research have shown that different neuropsychological variant of syndromes are possible, when children of different ages receive diagnosis of "attention deficit disorder" (Machinskaya et al, 2014;Glozman & Shevchenko, 2014;Solovieva & Quintanar, 2014a, 2015a.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is not correct to suppose that each cases of attention deficit disorder have always the same constellation of symptoms, central mechanisms and actions. Previous experience and research have shown that different neuropsychological variant of syndromes are possible, when children of different ages receive diagnosis of "attention deficit disorder" (Machinskaya et al, 2014;Glozman & Shevchenko, 2014;Solovieva & Quintanar, 2014a, 2015a.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios de EEG a partir del aná-lisis cualitativo visual han identificado ausencia de diferencias significativas entre el estado de desarrollo cortical de niños preescolares y escolares diagnosticados con TDAH y niños del grupo control (Machinskaya, Semenova, Absatova, & Sugrobova, 2014;Machinskaya, Sugrobova, & Semenova, 2015;Solovieva, Machinskaya, Quintanar, Bonilla, & Pelayo, 2009). Lo anterior descarta una relación unilateral de esta dificultad con el trastorno ejecutivo en la infancia.…”
Section: Síntomas De Inatención E Hiperactividad-impulsividad Que Carunclassified
“…En otros estudios se reportan evidencias obtenidas con empleo de técnicas de neuroimagen (Dickstein, Bannon, Castellanos, & Milham, 2006;Emond et al, 2009;Rubia et al, 2009) sobre la diversidad de bases cerebrales del TDAH. Se reporta que los síntomas del TDAH pueden ser situados no sólo en sectores frontales, pues se encuentran alteraciones en otras zonas corticales como el giro precentral (Quintanar et al, 2011) (Proal et al, 2013) y se refiere además la incidencia de estructuras subcorticales en distintos niveles (Machinskaya et al, 2014).…”
Section: Iscusiónunclassified
“…The elementary school period is as well characterized for the functional maturation of brain structures that provide downward modulation from specific frontal lobe areas, taking part during the visuospatial information processing (Machinskaya, Semenova, Absatova, & Sugrobova, 2014). The spatial analysis and synthesis mechanism, located on the second brain unit, guarantees the perception and production of essential features and their location (analytical component) as well as the perception and production of forms, the metric aspects and proportions of the objects (global component) ).…”
Section: Introductionmentioning
confidence: 99%